What Changes in Restaurant Satisfaction during Covid-19? An Overview Based on Online Reviews - Farinha, Carlos Silva; Borges Tiago, Flávio Gomes; Moreira Avelar, Sónia Margarida; Borges Tiago, Maria Teresa (Journal of Tourism, Sustainability and Well-being, 2023)
Lately, online users have become avid content creators and consumers of brands and firms through reviews. These serve as sources to peers and reflect reviewers’ satisfaction levels with different elements of the experiences. Thus, online reviews are considered reliable sources of information to understand customers’ perceptions. Using hybrid methodologies and text-mining techniques is recommended to obtain useful knowledge based on user-generated data. This study intended to understand customers’ perceptions of restaurant service and unveil any change that might occur driven by the COVID-19 pandemic. Therefore data was collected on TripAdvisor for two different periods - before and after the pandemic, using the top restaurants of two island tourism destinations. An upturn in customer satisfaction during Covid-19 and changes in attribute weight in the overall evaluation was observed. Therefore, the attribute “service” acquires even more special relevance. This methodology is considered adequate to meet the objectives defined, allowing to obtain relevant conclusions; it might also be applied to other phenomena and sectors.